Metode Inokulasi dan Pengamatan Perkembangan Phytophthora palmivora Serta Gejalanya Sebagai Penyebab Penyakit Busuk Buah Kakao (Theobroma cacao L.) - Dian Sri Anugrah; Umrah Umrah; Asrul Asrul (Biology Department, Mathematics and natural science, Tadulako University, 2017)
Phytopthora palmivora is one of pathogenic mushroom causes black pod iisease of cocoa plant. The research about P. palmivora development and symptoms as the cause black pod disease of cocoa (Theobroma cacao L.) was conducted from March until August 2016. Inoculation treatment of P. palmivora compared with aquades qontrols carried on cocoa fruit, with use “singlespot” and “polyspot” method. Observation parameters include incubation periode, extensive spotting, the percentage of P. palmivora infection and observation of macroscopic and microscopic P. palmivora mushroom. The results showed that in P. palmivora infection attack on cocoa fruit tends to grow up from third day to seventh day with average extensive spotting infection start on third day to seventh day are 6,4 cm, 8,1 cm, 9,6 cm, 12,72 cm, and 12,20 cm. Extensive spotting average P. palmivora infection most big is 14,22 cm while the percentage average most big is 90% and macroscopic structure showing their blackish brown spot on fruit surface and derived morphological characters of the hyphae are not insulated and ramified. Visible mycelium, clamydospores, papilla, zoospore dan sporangium forms such as Pier fruit on microscopic observation.